Pengaruh Budaya Organisasi Dan Pengawasan Terhadap Disiplin Kerja Pegawai Pada Dinas Sosial Kabupaten Bima - Annisah, Nur; Kusumayadi, Firmansyah; Amar, Khairul (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of organizational culture and supervision on employee work discipline at the Bima Regency Social Service. The type of research used in this research is associative research. The research instrument used in this research was a Likert scale questionnaire. The total population is 73 employees consisting of 37 civil servants, 4 P3K people, 13 honorary people, 19 main support staff (TPU). The sample for this research was 37 civil servants with a sampling technique, namely purposive sampling. Data collection in this research used observation, interviews, questionnaires and literature study. The data that has been collected will be analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, multiple correlation coefficients, determination tests, t tests and f tests. The research results show that organizational culture and supervision have a partial and simultaneous influence on employee work discipline at the Bima Regency Social Service.